THE INFLUENCE OF INTEGRATED DISTRIBUTION AND EXPORT DOCUMENT SUPPORTING SERVICE AT PT BAKHTERA TRANS CARGO SEMARANG - Novida Widarani; Umar Farouk; Andi Setiawan (Politeknik Negeri Semarang, 2017)
This research aims to analyze the influence of Integrated Distribution and Export Document Supporting Service on Overall Service Excellence Perception at PT Bakhtera Trans Cargo Semarang. The technique of analysis used in this research was multiple linear regression analysis. This research used questionnaire as the primary data. The amount of respondents are 46 who are customers of PT Bakhtera Trans Cargo Semarang. Based on the research that had been done, the independent variables (Integrated Distribution –X1 and Export Document Supporting Service –X2) effected the dependent variable (Overall Service Excellence Perception –Y) either stimultaneously and partially. The result of F-test shows that F sig. value about (0,000) < significance level (α=0,05). It means that the independent variables had significant effect on the dependent variable stimultaneously. Based on the t-test result, partial Integrated Distribution had significant and positive effect on Overall Service Excellence Perception with sig. value about (0,008)< α = 0,05 sig. level and coefficient of 0,279. Export Document Supporting Service had significant and positive effect on Overall Service Excellence Perception with sig. value about (0,000)< α = 0,05 sig. level and coefficient of 0,663. Based on the adjusted R-squared (R2) value about 0,565, which means 56,6% change in Overall Service Excellence Perception at PT Bakhtera Trans Cargo Semarang could be explained by two independent variables that were Integrated Distribution and Export Document Supporting Service. While the rest of 43,5% was explained by other factors.